Managing financial resources for effective NGO operations the case of selected Iloilo City based NGOs - Abitang, Tina Marie; Aguirre, Maria Louvie G.; Paciente, Julius C.; Peralta, Marco C. (2004.)
This study, entitled "Managing Financial Resources for Effective NGO Operations: The case of Selected Iloilo City based NGOs" attempted to answer the question "Does the management of financial resources lead to effective organizational operations for Iloilo City-based NGOs?" It made use of interview schedule with follow up questions to clarify things up. There were five respondents in the study namely: Green Forum-Western Visayas; I-CODE; PROCESS Foundation; Iloilo People's Habitat; and PRDCI. All of the respondents generate funds mainly from grants and donations. The allocation of their funds is affected by their aim and the type of projects they implement. In mobilizing their funds, they see to it that allocated funds for that certain projects is spent in accordance with the budget. If their funds are not enough to fince their activities, they implement strategies such as efficient use of resources, cost cutting, and voluntary service. For project operations, the respondents stated that the funds in implementing their projects are in accordance with the budget. Eventhough their financial resources are limited still, they are able to survive and have effective organizational operations through proper management of financial resources.
Research Paper (Mgt 199-Management Research) -- [Iloilo City] : University of the Philippines in the Visayas, College of Management, March 19, 2004.